Die Spuren der Vulgata in der mittelhochdeutschen Handschrift "Eisenach Ms. 1361-50" - Ilnicka, Jana (Vulgata in dialogue, 2022)
Among the medieval translations of the Bible into the vernacular languages, thePsalms occupy a special place. In Middle High German, however, from today's perspectivethey often seem somewhat awkward and almost naïve in their pious Christianising efforts. Oncloser analysis, however, one can see that there are two types of such texts: the ones are indeedtranslations that reproduce the original fairly accurately; the others are more like study textsthat take into account not only both Jerome translations of the Psalms, but also the contempo-rary commentaries